2014
DOI: 10.1186/s13054-014-0521-1
|View full text |Cite
|
Sign up to set email alerts
|

Risks to emergency medical responders at terrorist incidents: a narrative review of the medical literature

Abstract: As the threat of international terrorism rises, there is an increasing requirement to provide evidence-based information and training for the emergency personnel who will respond to terrorist incidents. Current major incident training advises that emergency responders prioritize their own personal safety above that of the ‘scene and survivors’. However, there is limited information available on the nature of these threats and how they may be accurately evaluated. This study reviews the published medical litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 100 publications
(107 reference statements)
0
22
0
3
Order By: Relevance
“…Regarding the strength of evidence of the management challenges, articles related to direct and indirect threats to safety on scene, [54] and issues concerning blast injuries with implications during assessment, triage, and treatment had higher scientific quality [10,11,78,80,101]. The scientific quality of the articles varied, partly due to the difficulties of studying an issue where circumstances and occurrence cannot be foretold or controlled (effecting study design).…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the strength of evidence of the management challenges, articles related to direct and indirect threats to safety on scene, [54] and issues concerning blast injuries with implications during assessment, triage, and treatment had higher scientific quality [10,11,78,80,101]. The scientific quality of the articles varied, partly due to the difficulties of studying an issue where circumstances and occurrence cannot be foretold or controlled (effecting study design).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…In a systematic review, Thompson et al further showed that while the scene of a terrorist attack includes direct threats, the published literature suggests that dominant causes of mortality and morbidity in responders after such incidents have been due to indirect environmental hazards [54].…”
Section: Being Aware Of Risks and Having Realistic Expectations Of Safetymentioning
confidence: 99%
“…Es werden stationäre, dynamische und multiple Szenarien unterschieden. Eine besondere Bedrohung bedeutet der "Second Hit": Dabei sind Hilfs-und Einsatzkräfte, die nach einem Anschlag an die Einsatzstelle eilen, durch eine zweite oder dritte Attacke bedroht [8].…”
Section: Verschiedene Szenarienunclassified
“…Terrorist events, such as the World Trade Center (WTC) attacks, present unique challenges to responders who can be exposed to both direct terrorist threats and indirect threats from environmental hazards such as airborne particles, structural collapses, fires, psychological stress and blood‐borne pathogens . A relatively low HCV prevalence among firefighters and EMS performing their usual duties does not preclude the possibility of a spike in blood‐borne infections in relation to work at mass casualty events, based on the particulars of the disaster.…”
Section: Introductionmentioning
confidence: 99%